FAKTOR FAKTOR PENENTU KEPUASAN KERJA TENAGA KERJA BALI YANG BEKERJA DI KAPAL PESIAR (STUDI KASUS DI CARNIVAL CRUISE LINE) - I Wayan Sunarsa (Institut Pariwisata dan Bisnis Internasional, 2010)
Job satisfaction is the attitude and feeling of someone towards his job. When an employee feels job satisfaction, he will be well motivated and productive. The Balinese workforces who work on board the cruise ships need a job satisfaction guarantee. This study aims at; (1) identifying factors that determine job satisfaction of Balinese workforces who work on board the cruise ships, (2) identifying the difference of job satisfaction between those who earns from tipping system and non-tipping system, and between those who have been marriage and single marital status. The factors that were investigated were job condition factor that consists of six variables; compensation factor that consists of six variables; supervision factor that consists of four variables; opportunity for achievement, recognitions, responsibility and challenging’s job factors that consists of three variables.The study was conducted at PT Cemerlang Tunggal Inti Karsa (CTI) Bali branch that is located on Tukad Jinah Street 2X Renon Denpasar Bali. The research made use non-probability sampling technique and used 230 respondents that were purposivelyselected. Questionnaires were used to collect the data, and then it was analyzed by using software tool analysis, SPSS ver. 13.Validity and reliability of instrument analysis revealed that the KMO value for all variables were above 0.05 with significance value 0.000. These values can be interpreted that the instrument used were valid and reliable. The findings of the study were; firstly the factors that determine the job satisfaction of Balinese workforces who worked on board the cruise ship were the opportunity for achievement factor with variance value 79.53; recognition factor with variance value 79.13; challenging’s job factor with variance value 74.57; supervision factor with variance value 70.32; responsibility factor with variance value 67.32, compensation factor with variance value 64.73; and job condition factor with variance value 61.74. Secondly, there were significant differences between those who earns from tipping system and non-tipping system, and there were not significant differences between those who have been marriage and single marital status.